R-Ras Glucosylation and transient RhoA activation determine the cytopathic effect produced by Toxin B variants from Toxin A-negative strains of clostridium difficile - Chaves-Olarte, Esteban (2003)
Clostridium difficile induces antibiotic-associated diarrhea through the production of toxin A and toxin B; the former toxin has been assumed to be responsible for the symptoms of the disease. Several toxin A-negative strains from C. difficile have recently been isolated from clinical cases and have been reported to produce toxin B variants eliciting an atypical cytopathic effect. Ultrastructural analysis indicated these toxins induce a rounding cytopathic effect and filopodia-like structures. Toxin B variants glucosylated R-Ras, and transfection with a constitutively active mutant of this GTPase protected cells against their cytopathic effect. Treatment of cells with toxin B variants induced detachment from the extracellular matrix and blockade of the epidermal growth factor-mediated phosphorylation of extracellular-regulated protein kinases, demonstrating a deleterious effect on the R-Ras-controlled avidity of integrins. Treatment with toxin B variants also induced a transient activation of RhoA probably because of inactivation of Rac1. Altogether, these data indicate that the cytopathic effect induced by toxin B variants is because of cell rounding and detachment mediated by R-Ras glucosylation, and the induction of filopodia-like structures is mediated by RhoA activation. Implications for the pathophysiology of C. difficile-induced diarrhea are discussed.